ECONOMETRIC MODELING OF ATTRACTING FOREIGN INVESTMENTS TO KEY SECTORS OF THE ECONOMY THROUGH MANAGING UZBEKISTAN'S PLACE IN INTERNATIONAL INDICES AND RATINGS (World Economics and Finance Bulletin, 2026)
This article analyzes the impact of foreign direct investment (FDI) on key economic sectors by managing Uzbekistan's position in international indices and rankings. The study uses statistical, econometric, and comparative analysis methods to identify the relationship between the Doing Business and Global Competitiveness indices and FDI volume. Also, comparing Uzbekistan with neighboring countries allows us to assess the country's competitiveness and develop strategic recommendations. Based on the results of the study, it is recommended to increase FDI volume by improving the indices and optimizing investment policy.
Keywords: Uzbekistan; foreign investments; FDI; Doing Business